1994
DOI: 10.1007/bf00283261
|View full text |Cite
|
Sign up to set email alerts
|

Allelic divergence in the human insulin gene provides evidence for intragenic recombination events in the non-coding regions: evidence for existence of new alleles

Abstract: Intragenic polymorphism of the human insulin gene (INS) was investigated in Korean subjects. The 1.9 kb INS sequence, including the 5' to 3' flanking regions, was amplified using the polymerase chain reaction (PCR), and analyzed by direct sequencing. All nucleotide sequences in the coding regions were the same as INS sequences previously reported, and four nucleotides, at positions +216, +1045, +1367, and +1380 in the non-coding regions, were found to be polymorphic. In addition to the previously identified po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The allele frequency of the alpha allele, although haplotypes were not examined, is reported to be 92% in Japanese and 77% in southern Indian subjects (16,17). An alpha allele is also reported to be dominant in Korean (13). There appears to be a difference in the frequency of these alleles in the insulin gene between Asians and other ethnic groups.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The allele frequency of the alpha allele, although haplotypes were not examined, is reported to be 92% in Japanese and 77% in southern Indian subjects (16,17). An alpha allele is also reported to be dominant in Korean (13). There appears to be a difference in the frequency of these alleles in the insulin gene between Asians and other ethnic groups.…”
Section: Discussionmentioning
confidence: 84%
“…The frequency of Ϫ23T 3 A is reported to be about 30% in Europeans, suggesting that Africans may have a frequency which is similar to Europeans (6). Kim et al reported that the frequency of Ϫ23T 3 A is also high (89.6%) in Korean subjects (13). In these ethnic groups, the Japanese appear to have the highest frequency of this allele, based on currently available data.…”
Section: Discussionmentioning
confidence: 94%
“…Gene conversion events, which usually account for exchanges over short sequence tracts [31], have been mainly described and intensively investigated as mechanisms generating allelic diversity in highly polymorphic genetic systems, such as the loci encoding the class‐II cell surface antigens of the major histocompatibility complex in humans [32,33]. Both mechanisms have also been thought to account for genetic disorders in humans, such as sporadic Alzheimer disease cases [34] and diabetic pathology involving the gene encoding insulin [35].…”
Section: Discussionmentioning
confidence: 99%